PENELITIAN BIOSTRATIGRAFI MESOZOIKUM PULAU ROTE, NUSA TENGGARA TIMUR - Fauzie Hasibuan (Pusat Survei Geologi, 2007)
A biostratigraphic study in Rote Island has proven that the distribution of Mesozoic rocks (especially Triassic, Jurassic,and Cretaceous) are broader than was thought by previous workers. The Paleozoic rocks are not exposed, but somefossils collected from the surface suggest that such rocks are present deep down in the earth subsurface of this island.The fossils were brought to the surface along with other materials by mud volcanoes which are common on the island.Mesozoic biostratigraphy of the Rote Island begins with Triassic, followed by Jurassic up to Cretaceous which areindicated by the presence of its fossils. Timorites sp., an ammonite genus indicating Permian (Paleozoic), yet theformation from which it originated is not known.In Mesozoic time, some species of Halobia lived indicating a Carnian to Early Norian age as shown by the presence of H.(H.) austriaca, H. (H.) styriaca, and H. (H.) charlyana in the Aitutu Formation. The presence of Monotis (M.) salinariashows that the Aitutu Formation is up to Late Norian in age. Fossil association is found in the Wailuli Formation,consisting amongst others of Ostrea sp., Perisphinctes timorense, Belemnopsis moluccana, B. galoi, B. stolleyi,Orbyrhynchia sp. and Irianites sp. Irianites sp. which indicates Bathonian is also found in the coeval formation in SulaIslands. Perisphinctes is generally found in Late Oxfordian. Belemnopsis moluccana has an age range from EarlyOxfordian to Early Tithonian, B. galoi from Kimmeridgian to Late Tithonian, and B. Stolleyi from Early Tithonian toBerriasian.The Nakfunu Formation exposed in Termanu area has a Cretaceous age in Rote Island. The formation is rich in radiolariasuch as Dictyomitra sp. which indicates Albian (Early Cretaceous). Trace fossils such as a large paramoudra are alsofound. Samples of radiolaria-bearing rocks were also collected, but the materials have not been studied due to lack ofthe expertise in the Geological Survey Institute.Â Keywords: Biostratigraphy, Paleozoic, Mesozoic, Aitutu Formation, Wailuli Formation, Nakfunu Formation, Halobia, Monotis, belemnites, ammonites